2021
DOI: 10.4136/ambi-agua.2684
|View full text |Cite
|
Sign up to set email alerts
|

Payment for water-ecosystem services monitoring in Brazil

Abstract: The reduction of tropical forests has generated a loss of ecosystem services across the globe. In Brazil, essential biomes related to water provision (such as the Atlantic Forest and Savanna) have been degraded, compromising water-ecosystem services. Payment for water-ecosystem services (water PES) has been implemented as a tool to stimulate changes in the use and management of these areas. Many water PES projects have emerged in Brazil using forest restoration, aiming to improve water ecosystem services. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the first five years of project operation, USD 1.6 million was invested. In total, 4562 hectares of conservation areas and 564 hectares of restored area are now included in the follow-up monitoring, which is supported by 70 rural landowners [29][30][31][32][33][34].…”
Section: Brazil-water and Forest Producers Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first five years of project operation, USD 1.6 million was invested. In total, 4562 hectares of conservation areas and 564 hectares of restored area are now included in the follow-up monitoring, which is supported by 70 rural landowners [29][30][31][32][33][34].…”
Section: Brazil-water and Forest Producers Projectmentioning
confidence: 99%
“…In Brazil, interviews and meetings were conducted with relevant stakeholders who are currently working on monitoring and evaluating the implementation of the NBS project. In addition, reports and academic literature were consulted [29][30][31][32][33]. In Norway, the context was assessed by drawing upon reports and publicly available databases.…”
Section: Application Of the Framework To The Case Studiesmentioning
confidence: 99%
“…The biggest challenges in developing mechanisms for PES programs have been the slow process in building confidence between that who pays and the one who receives, as well as being clear on additional gains between the parties (Asquith et al, 2008). Furthermore, holistic monitoring that deals with the ecosystem as a complex socio-economic system is necessary (Lima et al, 2021). In the Brazilian Midwest, in the Guariroba Environmental Protection Area, preliminary results showed that the baseflow tended to increase and soil conservation practices reduced the soil erosion by a quarter, results which were positive for water availability and considering the particularities of land use combined with water supply characteristics of the reservoir (Sone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%